Acute Fibrinous and Organizing Pneumonia Related to Rituximab: An Entity to Recognize: Pneumonia Organizativa Fibrinosa Aguda Induzida pelo Rituximab: Uma Entidade a (Re)conhecer - Couto, Alexandra; Almeida, Marta; Marques, Herlander; Nabiço, Rui; Rolo, Rui; Cunha, João; Pardal, Fernando; Carvalho, Sofia (Gazeta Médica, 2017)
Acute fibrinous organizational pneumonia is a histological entity included in the group of interstitial lung diseases, with multiple etiologies including pharmacological toxicity. The authors describe the case of a 73-year-old man diagnosed with lymphoplasmacytic lymphoma under maintenance treatment with rituximab after chemotherapy. The patient developed an insidious clinical picture characterized by non-productive cough, dyspnea and asthenia. The integration of imaging aspects and pulmonary biopsy histology led to the diagnosis of acute fibrinous and organizing pneumonia. After suspension of the drug and institution of corticosteroids, the patient presented a favorable clinical and imaging course. Given the increasing use of targeted therapies in oncology, the present case aims to contribute to the recognition of this entity as a potential adverse event. Received: 07/06/2017 - Accepted: 30/08/2017